Digital Public Relations dalam Mempertahankan Citra Lembaga Administrasi Negara: Studi Deskriptif Kualitatif pada Media Sosial LAN RI - Ikhsan Meidian Utama; Sa’diyah El Adaiyah (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
In an era of increasingly open and developing information, the image of state institutions is a reflection of a government and can affect public trust. Therefore, LAN RI Public Relations carries out Digital Public Relations activities using social media so that LAN RI can maintain its image in the eyes of the public. The purpose of this research is to describe Regina Luttrel's SOME theory in the activity of using social media in maintaining the image of the institution. The theory used in this research is the SOME theory which has the dimensions of Share, Optimize, Manage, and Engange (Regina Luttrell). This research also uses image theory which consists of Perception, Cognition, and Motive dimensions (Walter Lippmann). This study concludes that LAN Public Relations in the Concept of The Circular Model of SOME implements Share by utilizing various social media platforms. Content is organized through a curation process that is tailored to the institution's guidelines to create relevant and informative communication. Through Optimize, the effectiveness of message delivery is measured based on data analytics with strategies that consider platform algorithms. In the Manage stage, LAN's PR team monitors and analyzes emerging issues, ensuring a quick response to sensitive issues. Engage efforts are demonstrated through surveys, quizzes, discussion forums, and employee personal branding efforts that strengthen public engagement while building trust.